FUNGSI KOORDINASI TERHADAP PELAKSANAAN PEMERINTAH DI KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Gusni Ayu; Irwan Irwan; Adam Latif; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aimed to determine the effect of the coordination function on the implementation of government in Watang Sidenreng District, Sidenreng Rappang Regency. The population in this study were 31 sub-district office apparatus and the head of the Watang Sidenreng sub-district environment, the sampling period used was saturated sampling (census) with the technique of determining the sample if all population members were used as a sample of 31 people, this study used a Quantitative Descriptive Method. Data collection techniques are used through observation, interviews, questionnaires, and library research. The data analysis techniques used are Descriptive Statistics, Data Quality Test, using the Frequency Table and Likert Scale. The results of this study showed that the influence of the Coordination Function Against Government Implementation in Watang Sidenreng District with a value of 61.41% is categorized as